Combination nivolumab and ipilimumab or nivolumab alone in melanoma brain metastases: a multicentre randomised phase 2 study. Issue 5 (May 2018) - Long, Georgina V; Atkinson, Victoria; Lo, Serigne; Sandhu, Shahneen; Guminski, Alexander D; Brown, Michael P; Wilmott, James S; Edwards, Jarem; Gonzalez, Maria; Scolyer, Richard A; Menzies, Alexander M; McArthur, Grant A
Summary: Background: Nivolumab monotherapy and combination nivolumab plus ipilimumab increase proportions of patients achieving a response and survival versus ipilimumab in patients with metastatic melanoma; however, efficacy in active brain metastases is unknown. We aimed to establish the efficacy and safety of nivolumab alone or in combination with ipilimumab in patients with active melanoma brain metastases. Methods: This multicentre open-label randomised phase 2 trial was done at four sites in Australia, in three cohorts of immunotherapy-naive patients aged 18 years or older with melanoma brain metastases. Patients with asymptomatic brain metastases with no previous local brain therapy were randomly assigned using the biased coin minimisation method, stratified by site, in a 30:24 ratio (after a safety run-in of six patients) to cohort A (nivolumab plus ipilimumab) or cohort B (nivolumab). Patients with brain metastases in whom local therapy had failed, or who had neurological symptoms, or leptomeningeal disease were enrolled in non-randomised cohort C (nivolumab). Patients in cohort A received intravenous nivolumab 1 mg/kg combined with ipilimumab 3 mg/kg every 3 weeks for four doses, then nivolumab 3 mg/kg every 2 weeks; patients in cohort B or cohort C received intravenous nivolumab 3 mg/kg every 2 weeks. The primary endpoint was intracranial response from week 12. Primary and safety analyses were done on an intention-to-treat basis in all patients who received at least one dose of the study drug. This trial is registered withClinicalTrials.gov, numberNCT02374242, and is ongoing for the final survival analysis. Findings: Between Nov 4, 2014, and April 21, 2017, 79 patients were enrolled; 36 in cohort A, 27 in cohort B, and 16 in cohort C. One patient in cohort A and two in cohort B were found to be ineligible and excluded from the study before receiving the study drug. At the data cutoff (Aug 28, 2017), with a median follow up of 17 months (IQR 8–25), intracranial responses were achieved by 16 (46%; 95% CI 29–63) of 35 patients in cohort A, five (20%; 7–41) of 25 in cohort B, and one (6%; 0–30) of 16 in cohort C. Intracranial complete responses occurred in six (17%) patients in cohort A, three (12%) in cohort B, and none in cohort C. Treatment-related adverse events occurred in 34 (97%) of 35 patients in cohort A, 17 (68%) of 25 in cohort B, and eight (50%) of 16 in cohort C. Grade 3 or 4 treatment-related adverse events occurred in 19 (54%) patients in cohort A, four (16%) in cohort B, and two (13%) in cohort C. No treatment-related deaths occurred. Interpretation: Nivolumab combined with ipilimumab and nivolumab monotherapy are active in melanoma brain metastases. A high proportion of patients achieved an intracranial response with the combination. Thus, nivolumab combined with ipilimumab should be considered as a first-line therapy for patients with asymptomatic untreated brain metastases. Funding: Melanoma Institute Australia and Bristol-Myers Squibb.